Childress, Clayton, Under the Cover: The Creation, Production, and Reception of a Novel, Princeton: Princeton University Press, 2017 - Norrick-Rühl, Corinna (Mémoires du livre / Studies in Book Culture, 2026)
This retrospective review examines Clayton Childress’s Under the Cover: The Creation, Production, and Reception of a Novel (Princeton: Princeton University Press, 2017), a milestone study in the sociology of culture with significant implications for book and publishing studies. Childress traces a single work of literary historical fiction—Cornelia Nixon’s Jarrettsville (2009)—across the interconnected fields of creation, production, and reception, offering an integrated model that remains an exception in its methodological ambition. The review highlights three chapters of particular value for researchers and teachers in book studies, and situates Under the Cover within the broader interdisciplinary conversation it has helped to generate since its publication.